Expert F# 4.0 - Syme, Don; Granicz, Adam; Cisternino, Antonio (Apress, 2016)
F# 4.0 achieves unrivaled levels of programmer productivity and program clarity across multiple platforms including Windows, Linux, Android, OSX and iOS as well as HTML5 and GPUs. Learn from F#'s inventor to become an expert in the latest version of this powerful programming language.